Agronomic characters in asparagus of different ages and crop systems - Asprelli, Pablo Diego; Anido, Fernando Sebastián López; Cointry, Enrique Luis (Pesquisa Agropecuaria Brasileira, 2005)
Age and crop system effects on agronomic response were evaluated in 11 hybrids of Asparagus officinalis L. The experimental design was a complete randomized block with three replicates of 20 plants of 3 or 4 years old, conducted either in mounded soil over plants for blanched asparagus, or in raised beds without ridging for green asparagus. The highest mean values were obtained under the blanched production for days to harvest, market yield, total yield, spears number and the spear mean weight. However, under the green production, the rate of increment from first to second year was superior for market yield and total yield due to an augmented rate of increment of spears number. Type and year of production effects were similar for days to first harvest and spears mean weight, meanwhile days to 50% of sprout plot was affected mainly by the year of production